PENGARUH PEMAHAMAN, PENGETAHUAN DAN TAX AMNESTY TERHADAP KEPATUHAN PEMBAYARAN PAJAK ORANG PRIBADI - Lailatul, Ida; Nurlaela, Siti; Masitoh, Endang (Prosiding Seminar Nasional: Manajemen, Akuntansi, dan Perbankan; Vol 1 No 1 (2018): Prosiding Seminar Nasional dan Call for Papers Manajemen, Akuntansi, dan Perbankan 2018, 2018)
This study was conducted to determine the effect of understanding, knowledge, and tax amnesty on compliance of tax payments of individuals registered in KPP Pratama Surakarta. The dependent variable in this research is taxpayer compliance of individual person and the independent variable in this research is knowledge of taxpayer, understanding of taxpayer, and tax amnesty. The population in this research is individual taxpayer registered in KPP Pratama Surakarta. Sampling technique that is by using method of convenience sampling. The sample used in this research  of 98 respondents. The data has been collected by issuing questionnaires and using likert scale 1 to 5. The method used in this research is quantitative with multiple linear analysis model. Based on the result of analysis, it shows that the understanding, knowladge and tax amnesty significant effect on compliance of tax payments of individuals.